2021
DOI: 10.2174/1570162x18666200908112113
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Profiling in HIV, HCV, and HIV/HCV Co-Infected Patients

Abstract: Background: Human immunodeficiency virus (HIV) an hepatitis C virus (HCV) infections are important public health issues. Objective: This study aimed to assess the association between microRNAs expression level and immunological and viral markers in HIV, HCV, and HIV/HCV coinfected patients. Method: The expression level of miR-29, miR-149, miR-199, miR-let7, miR-223, miR-155, miR-122, and miR-150 was evaluated in 20 HIV, 20 HCV, 20 coinfected patients and 20 healthy controls using real-time PCR assay. HIV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
2
12
0
1
Order By: Relevance
“…Therefore, miR-122-5p downregulation might allow COPA and OSBP expression in HIV/HCV patients, promoting HCV replication in PBMCs. In line with our results, Moghoofei et al 2021 also reported that hsa-miR-122-5p was differentially expressed in PBMCs of both HIV, HCV and HIV/HCV patients [17]. These outcomes indicate that both HCV and HIV influence the expression of hsa-miR-122-5p not only in liver cells but also in PBMCs.…”
Section: Hiv/hcv+ Mirna Profilesupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, miR-122-5p downregulation might allow COPA and OSBP expression in HIV/HCV patients, promoting HCV replication in PBMCs. In line with our results, Moghoofei et al 2021 also reported that hsa-miR-122-5p was differentially expressed in PBMCs of both HIV, HCV and HIV/HCV patients [17]. These outcomes indicate that both HCV and HIV influence the expression of hsa-miR-122-5p not only in liver cells but also in PBMCs.…”
Section: Hiv/hcv+ Mirna Profilesupporting
confidence: 91%
“…To date, only scarce data have been published regarding the miRNA profile of HIV/HCV patients [ 17 , 18 ], none of them with a massive approach and even less focused on spontaneous clarifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-122 is the only miRNA that was found to be associated with each of these conditions. [42][43][44][45][46][47][48][49][50][51][52][53] As one of the earliest examples of tissue-specific miRNAs, miR-122 is of heightened interest as a marker of liver injury. 80,81 Upon its discovery, investigators found that mir-122 accounted for 72% of all miRNAs cloned from the livers of mice.…”
Section: Mirnas As Markers Of Injurymentioning
confidence: 99%
“… miR-155 46 ⇧ 🅜  miR-29 46 ⇩ 🅜  miR-223 46 ⇩ 🅜  miR-199 46 ⇧ 🅜  miR-122-5p 46,47 ⇧ 🅜  miR-449a 57 ⇧ 🅣  miR-885-5p 58 ⇧ 🅢  miR-122 59 ⇧ 🅢…”
Section: Hepatitis C Virusunclassified
“…Major limitations include the absence of studies implementing computational models to identify these miRNAs, technical issues associated with conventional miRNA extraction and detection tools, and scarcity of anal cancer in vitro and in vivo models. Ongoing studies are still being conducted to study miRNA profiles during HIV[ 125 - 127 ] and HPV[ 128 - 130 ] infections. With the appropriate application of advanced bioinformatic analysis tools and computational models, the identification of the most predictive miRNAs, even from complex datasets would be possible.…”
Section: Limitations and Considerations For The Use Of Mirnas As Biomarkers For Anal Cancer Screeningmentioning
confidence: 99%